A Novel Implementation of Krasnoselskii’s Fixed-Point Theorem to a Class of Nonlinear Neutral Differential Equations - Ali Rezaiguia; Abdelkader Moumen; Abdelaziz Mennouni; Mohammad Alshammari; Taher S. Hassan (Journal of Function Spaces, 2022)
In this work, we examine a class of nonlinear neutral differential equations. Krasnoselskii’s fixed-point theorem is used to provide sufficient conditions for the existence of positive periodic solutions to this type of problem.